CYBERCRIMINAL PERSONALITY: CRIMINOLOGY-TYPOLOGICAL CHARACTERISTICS (Bulletin of criminological association of Ukraine, 2025)
The article examines criminological approaches to the typology of cybercriminals in the context of the rapid escalation of threats in the digital environment. The emphasis is on the need to rethink traditional provisions of criminological theory in the context of the post-industrial development of society, in particular due to the complexity of the structure of cybercrime and the growth of its impact on social relations. The importance of a deep analysis of the criminal's personality as a key element for the development of effective prevention measures is emphasized. The need to form a typology of cybercriminals is substantiated, which allows identifying common features, motives and behavioral models of persons committing criminal offenses in cyberspace. An overview of scientific approaches to the problem is provided, and the difficulties of identifying typical profiles of criminal offenders in connection with the specifics of cybercrime are analyzed. Particular attention is paid to the study of the personal, psychophysiological and social characteristics of cybercriminals.
Keywords: cybercrime; criminological typology; criminal offender personality; computer crimes; digital environment; criminally unlawful behavior; psychological characteristics; counteraction to cybercrime